Jamu Pelangsing Galian Singset Bermanfaat Sebagai Antiobesitas dan Antilipidemia pada Tikus (JAMU GALIAN SINGSET USEFUL AS AN ANTIOBESITY AND ANTILIPIDAEMIA IN RATS) - Marta, Ice Lusia; Darusman, Huda Shalahudin; Ekastuti, Damiana Rita (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Obesity and dyslipidemia are health problems that can increase the risk of cardiovascular disease. This study aims to analyze the potency of antiobesitas and antidislipidemia of jamu galian singset (JGS). The research method used complete randomized design with 8 treatment groups and 4 replications as follows: P1 (Standard Feed + Aquadest), P2 (Standard Feed + 200 mg Orlistat / kg BW), P3 (Standard Feed + 176,4mg JGS / 200g BW) P4 (Standard Feed + 352,8mg JGS / 200 g BW), P5 (High Fat Feed + Aquadest), P6 (High Fat Feed + 200 mg Orlistat / kg BW), P7 (High Fat Feed + 176,4 mg JGS / 200 g BW) and P8 (High Fat Feed + 352,8 mg JGS / 200 g BW). The parameters observed were feed intake, body weight gain, body weight gain ratio, fat intake, fat absorption, fat digestibility, feces fat, abdominal fat, muscle fat, body weight, body fat percentage and lipid profile, include Cholesterol total (TC), triglycerides (TG), HDL and LDL. The results showed that JGS significantly (P <0,05) decreased the body weight gain of the rat, the ratio of body weight gain per feed intake and the weight of abdominal fat. Giving JGS increases the absorption of fat, but not found high fat in the feces. Jamu galian singset has no effect (P> 0.05) on rat lipid profile. Baced on the results of this study it can be concluded that JGS can be used as antiobesity and more effectively decrease body weight gain on high fat diet than standard feeding diet. Jamu galian singset are suspected to have a different working mechanism with orlistat as antiobesitas.
Keywords: Kolesterol, HDL, jamu, LDL, trigliserida